PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE STOP THINK DO PADA MATERI KPK DAN FPB KELAS VI SDN TAHUNAN 1 TAHUN PELAJARAN 2017/2018 - Nurhayati, Rosidah; Daris, Daris; Aji, Styo Mahendra Wasita (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2023)
This study aims to improve Mathematics Learning Outcomes of Year 6 Elementary School students at New Year's Elementary School using the Stop Think Do Method on KPK and FPB Material 1 Academic Year 2017/2018. The type of research that researchers did included classroom action research (CAR). The place used in this study was the New Year 1 Public Elementary School, Kec. Tegalombo, Kab. Pacitan. The research subjects were aimed at grade 6 students at SDN Tahun Baru 1 Kec. Tegalombo, Kab. Pacitan Academic Year 2017/2018 as many as 19 students. The action research model used in this research is the research model created by Kemmis and Mc Taggart. The research instruments used in this study are; Test Questions, Observation Sheets, and Student Response Questionnaires to the implementation of learning. Data analysis in this study used a qualitative descriptive analysis technique. Learning Mathematics with the Stop Think Do method can improve the mathematics learning outcomes of Grade 6 students at SDN Tahun Baru 1 Kec. Tegalombo, Kab. Pacitan, this can be seen from the increase in the percentage of classical completeness from the previous cycle, namely in cycle I it reached 62.96% and cycle II reached 85.19%. Students are interested in learning mathematics using the Stop Think Do method, this can be shown by the student response reaching 87.90% with the title "very interested" in learning mathematics